Determinants of Labor Duration: A Systematic Review of Maternal, Fetal, And Healthcare Factors - Widya Maya Ningrum; Kurniati Devi Purnamasari; Silvia Widyani Heriyanti; Kartikasari Kartikasari (Journal of Midwifery and Public Health, 2025)
Prolonged labor increases risks of maternal and neonatal complications. Identifying its determinants is essential for improving intrapartum care. This systematic review synthesizes evidence on maternal, fetal, and healthcare factors influencing labor duration. A systematic search was conducted in Google Scholar, PubMed, and ScienceDirect for articles published between 2015–2025. Studies reporting original data on labor duration determinants were included. Fifteen studies met inclusion criteria. Maternal factors (advanced age >35 years, nulliparity, high anxiety) consistently prolonged labor. Fetal factors including macrosomia (>4000 g) and occiput posterior malposition significantly extended labor duration. Healthcare factors such as continuous labor support, maternal mobilization, and appropriate oxytocin use were associated with shorter labor duration. Labor duration is determined by multifactorial interactions. Evidence-based, comprehensive intrapartum care addressing all determinant categories is recommended to optimize maternal and neonatal outcomes.